Obesity, Diet and Risk of Non-Hodgkin Lymphoma - Skibola, Christine F. (2007)
Non-Hodgkin lymphoma (NHL) represents a group of heterogeneous diseases that significantly vary in their causes, molecular profiles, and natural progression. In 2006, there will be ~59,000 newly diagnosed NHL cases in the U.S. and over 300,000 cases worldwide. While new therapeutic regimens are minimizing the number of deaths related to NHL, causes for the majority of lymphomas remain undetermined. Recent studies suggest that dietary factors may contribute to the rising rates of NHL. This review will summarize epidemiological reports that have studied the relationship between obesity, physical activity, diet and risk of NHL. Based on a number of case-control and prospective cohort studies, overweight/obesity likely increases the risk of NHL; whereas, moderate physical activity may reduce risk. Several studies support an inverse association between intakes of vegetables and NHL risk, particularly for the consumption of cruciferous vegetables. This may relate to the induction of apoptosis and growth arrest in pre-neoplastic and neoplastic cells, two important actions of isothiocyanates found in cruciferous vegetables. Studies also suggest that fish intake may be inversely associated with risk of NHL, though findings have not been entirely consistent. This may relate to the high organochlorine content in some fish that could override a protective effect. High consumption of fats, meat and dairy products also may increase lymphoma risk. The accumulated scientific evidence concerning the associations between obesity, diet, and NHL suggests several identified modifiable risk factors that might be recommended to decrease lymphoma risk.